Financial Institutions’ Regulation, Banking Sector Competitiveness and Stability of the Banking Sector in Nigeria - Andrew EO Erhijakpor; Felicia Ogheneotegiri Eyamu (CV. Proaksara Global Transeduka, 2025)
The paper examined the effect of financial institutions’ regulation, banking sector competitiveness and stability of the banking sector in Nigeria from 1996 to 2021. The study disaggregated financial institution’s regulation into capital adequacy ratio, liquidity, and private sector credits, while the banking sector competitiveness was measured by Lerner Index. More so, stability of the banking sector was measured by Z-Score. The study embraced the Ex post facto research design. Data were collected for the twenty-one (21) DMBs from 1996 to 2021. Data were sourced from CBN statistical bulletin, CBN financial stability report and World Bank database, 2021. The Robust Least Square Estimation Technique was adopted. The regression estimate clearly revealed that, liquidity ratio, Capital Adequacy Ratio, and banking sector competitiveness have high contributive effect on the stability of Nigerian banks but private sector credits exposed banks to high incidence of bank instability. Hence, the paper concludes that, financial institution’s regulations, banking sector’s competitiveness are perquisite for the financial stability of banks in Nigeria within the reviewed periods. As such, the Apex bank should ensure that all the Nigerian banks should sustain the current minimum CAR of 15%. Lastly, Nigerian banks are encouraged to invest in income remunerative ventures as this have a high contributive effect on their financial stability.